Piperlongumine decreases cell proliferation and the expression of cell cycle-associated proteins by inhibiting Akt pathway in human lung cancer cells. (January 2018) - Seok, Jin Sil; Jeong, Chang Hee; Petriello, Michael C.; Seo, Han Geuk; Yoo, Hyunjin; Hong, Kwonho; Han, Sung Gu
Abstract: Piperlongumine (PL) is an alkaloid of a pepper plant found in Southeast Asia. PL is known to induce selective toxicity towards a variety of cancer cell types. To explore the possible anti-lung cancer effects of PL, A549 cells were treated with PL (0–40 μM) for 24 h. Alterations in the expression of cell cycle-associated proteins (cyclin D1, cyclin-dependent kinase 4 (CDK4), CDK6 and retinoblastoma (Rb)) and intracellular signaling molecules (extracellular signal receptor-activated kinase 1/2 (ERK1/2), Akt, p38 and nuclear factor-κB (NF-κB)) were examined in cells following treatment of PL using Western blot analysis. Results showed that proliferation of cells were significantly decreased by PL in a dose-dependent manner. Flow cytometry results demonstrated increased number of cells in G1 phase in PL (40 μM)-treated group. Reactive oxygen species was significantly increased in cells treated with PL at 20–40 μM. The expression of cyclin D1, CDK4, CDK6 and p-Rb were markedly decreased in cells treated with PL at 40 μM. Treatment of cells with PL suppressed phosphorylation of Akt but increased ERK1/2 phosphorylation. Treatment of PL significantly decreased nuclear translocation of NF-κB p65 in cells. These results suggest that PL possesses antiproliferative properties in A549 cells. Highlights: Piperlongumine decreases proliferation of A549 cells. The mechanism is through ROS generation and downregulated Akt pathway. Piperlongumine decreases protein expression of cycle-associated proteins.